2010
DOI: 10.1248/jhs.56.47
|View full text |Cite
|
Sign up to set email alerts
|

Speciation Analysis of Arsenics in Commercial Hijiki by High Performance Liquid Chromatography-tandem-mass Spectrometry and High Performance Liquid Chromatography-inductively Coupled Plasma Mass Spectrometry

Abstract: Edible brown alga (hijiki in Japanese, Hijikia fusiforme) contains not only a high content of inorganic arsenic (iAs) but also various arsenosugars (AsSugs) which are metabolized to dimethylarsinic acid (DMA) in mammals. Since DMA is considered to be carcinogenic in rodents, it is necessary to accurately measure the contents of AsSugs as well as iAs for the risk assessment of seaweed consumption. Seven commercially available dried-hijiki products and two raw hijiki products were analyzed. Total-As was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…As Nakamura et al ( 2008 ) pointed out, calculations of excess cancer risk assume that the mechanism of carcinogenesis has no threshold dose; i.e., the incidence of cancer is linearly related to As intake in a low dose range, and this may not be the case. Inorganic As and arsenosugar content of hijiki varies geographically and with manufacturing method (Shimoda et al 2010 ). Canada and the UK advise consumers to avoid eating hijiki (CFIA 2012 ; UK FSA 2016 ).…”
Section: Safetymentioning
confidence: 99%
“…As Nakamura et al ( 2008 ) pointed out, calculations of excess cancer risk assume that the mechanism of carcinogenesis has no threshold dose; i.e., the incidence of cancer is linearly related to As intake in a low dose range, and this may not be the case. Inorganic As and arsenosugar content of hijiki varies geographically and with manufacturing method (Shimoda et al 2010 ). Canada and the UK advise consumers to avoid eating hijiki (CFIA 2012 ; UK FSA 2016 ).…”
Section: Safetymentioning
confidence: 99%
“…Lai et al 13) reported that AsSug content in Fucus gardneri fluctuates by a season. In addition, Shimoda et al 14) reported that contents and types of AsSugs in Hizikia fusiforme varied according to the harvested area. Our sample was harvested from February to April in Sanriku Coast Japan.…”
Section: Discussionmentioning
confidence: 99%
“…The digested solution was measured using the standard addition method. Instrumental conditions for ICP-MS using the DRC mode were described in our earlier report (Shimoda et al, 2010). The method was validated by analysis of DORM-3 (fish protein from the National Research Council of Canada) (certified T-As = 6.88 ± 0.88 µg/g; found T-As = 6.91 ± 0.26 µg/g, n = 3).…”
Section: Determination Of Total Arsenic Content In Wakame Seaweedmentioning
confidence: 99%